1991
DOI: 10.1073/pnas.88.10.4498
|View full text |Cite
|
Sign up to set email alerts
|

A systematic mutational analysis of hormone-binding determinants in the human growth hormone receptor.

Abstract: A mutational strategy is presented that allowed us to identify hormone-binding determinants in the extracellular portion of the human growth hormone receptor (hGHbp), a 238-residue protein with sequence homology to a number of cytokine receptors. By systematically replacing side chains with alanine we probed the importance of charged residues (49 total, typically located on the surface), aromatic residues (9 total), and neighbors of these (26 total). The alanine substitutions that were most disruptive to hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
167
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(176 citation statements)
references
References 31 publications
7
167
1
1
Order By: Relevance
“…Several receptors in the cytokine receptor family have residues important for ligand binding located in the loop between the BЈ and CЈ ␤-strands (5,12,14). We have reported previously that Ser 152 in the BЈ-CЈ loop of the EPOR may have a role in EPO binding, based on the 16-fold increase in IC 50 value of the S152A-EBP (15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several receptors in the cytokine receptor family have residues important for ligand binding located in the loop between the BЈ and CЈ ␤-strands (5,12,14). We have reported previously that Ser 152 in the BЈ-CЈ loop of the EPOR may have a role in EPO binding, based on the 16-fold increase in IC 50 value of the S152A-EBP (15).…”
Section: Resultsmentioning
confidence: 99%
“…Single alanine substitutions in the C-D loop of the GHbp had only marginal effects on GH binding (14). However, alanine substitutions of residues within the C-D loop of the human IL-5R␣ (D55, Y57) abolished IL-5 binding (27).…”
Section: Table I Epo Binding Activity Of Mutations In the Extracellulmentioning
confidence: 99%
See 1 more Smart Citation
“…However, large portions of Arf1p, including those determined by crystallography to bind other proteins, have not been tested directly for their function in cells. In this study we have used a systematic clustered charge-to-alanine mutagenesis approach (Bass et al, 1991;Bennett et al, 1991;Gibbs and Zoller, 1991) to generate mutations widely distributed on the surface of Arf1p in yeast. This approach is unbiased by expectations based on structure or sequence homology to other GTPases and has been used successfully in the related Rho-family GTPase CDC42 to discover novel phenotypes and to identify regions essential for cellular function (Kozminski et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In many tissues, GHR generates two different mRNAs by an alternative splicing of exon 3, one for a full length receptor and the other for an isoform that lacks exon 3 (Urbanek et al, 1992;Sobrier et al, 1993;Mercado et aL, 1994). Although previous studies suggested that exon 3 is not necessary for GH binding, the functional significance of the splice variant without exon 3 remains unknown (Mercado et al, 1994;Bass et al, 1991). Several different GHR mutations have been reported among Laron syndrome patients of different ethnic origins.…”
Section: Introductionmentioning
confidence: 99%